Faktor yang Menentukan Implementasi Kebijakan Retribusi Jasa Usaha Pada Objek Wisata Lombongo di Kabupaten Bone Bolango - Bakari, Maimun; Tui, Fenti Prihatini; Nani, Yacob Noho (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to identify and describe the factors determining the implementations of retribution policy of business service at Lombongo tourist attractions in Bone Bolango Regency. The research employs a qualitative approach with a descriptive research design. Techniques of data collection include observation, interview, and documentation, while data analysis utilizes the Huberman model. Furthermore, the research focused on the factors influencing the implementation of retribution policy of business service at Lombongo tourist attractions, examined through communication, resource availability, implementer disposition/attitude, and bureaucratic structure. The results indicate that the factors determining the implementation of retribution policy of business service at Lombongo tourist attractions are not functioning optimally. Communication between implementers and target groups has been established well on a vertical level; however, there exist a gap between the information received and observations made in the field, necessitating further optimization. Resources factors- including human resources, facilities, and budget-require enhancement to improve the development of Lombongo tourist attractions. The disposition/attitude of implementers has not been optimal, as proved by visitors’ lack of awareness regarding retribution payments and the insufficient assertiveness of retribution collectors in carrying out their duties. In terms of bureaucratic structure, the system is functioning adequately, as indicated by clearly defined roles and responsibilities and the presence of standard operating procedures related to the collection of retribution in Bone Bolango Regency.